Bibliometric Analysis of The Development Map and Research Direction on Islamic Social Education in The Scopus Database (1978-2023) - Maksum, Muh. Nur Rochim; Shiddiqi, Ilham Jimly Ash; Azani, Mohammad Zakki; Andhim, Muk (Universitas Muhammadiyah Surakarta, 2023)
This study aims to determine the development and direction of Islamic Social Education research in publications indexed by Scopus. The study employs bibliometric analysis techniques to explore all publications on social Islamic Education indexed in the Scopus database from 1978 to 2023. The data was analyzed using Excel and R/R-Studio, and VOSviewer was used to perform visual analysis of the simultaneous occurrence of keywords and document citations. The author found 626 publications that fit the function, subject, and criteria set. The results show an annual growth rate of 9.27%, with the majority of publications on Islamic social education in 2022. Indonesia contributes the most publications, with the highest affiliation in Universiti Kebangsaan Malaysia. Hoechner, H is the most prolific writer on the theme of Islamic social education. The bibliometric analysis performed was limited to Scopus data only, and other national and international databases were not taken into account. This study presents a brief overview of the literature accessible to researchers working in education and provides recommendations for future research.